The impact of electroconvulsive therapy on the spatial QRS-T angle and cardiac troponin T concentration in psychiatric patients. - Michał Próchnicki; Grzegorz Rudzki; Michał Dzikowski; Andrzej Jaroszyński; Hanna Karakula-Juchnowicz (PLoS ONE, 2019)
BACKGROUND:Electroconvulsive therapy (ECT) is an effective treatment method used in psychiatry; however, its cardiac safety has not been clearly demonstrated. The aim of the study was evaluation of the ECT effects on the myocardium based on troponin T concentrations and the following ECG parameters: the spatial QRS-T angle (QRS-TA), QRS duration (QRSd) and the corrected QT interval (QTc). METHODS:In the study 44 patients (12 female and 32 male) were enrolled diagnosed with schizophrenia (n = 21) and major depressive disorders (n = 23), according to the DSM-IVR criteria. All cases were undergoing ECT procedures. The mean age of the patients was 36.9±16 years (range: 18-74). Resting ECG was recorded before performing ECG and 1 hour after. The spatial QRS-TA was reconstructed from 12-lead ECG using the inverse Dower method. Troponin T concentration was assessed before the procedure and 6 hours after ECT. RESULTS:No significant changes to troponin T concentrations were observed during the ECT series. The pre-ECT value of the spatial QRS-TA was 41.1±18.9°. The follow-up examinations did not reveal any significant increase of this parameter (p = 0.09) in any of the consecutive measurements. There were no significant changes in the QTc interval duration or the QRS complex duration demonstrated before the third, fifth and last procedure in the cycle (p>0.05). No significant changes to troponin T concentrations were observed during the ECT series. CONCLUSIONS:Our findings indicate a lack of negative ECT effects on the risk of adverse cardiovascular events measured by the spatial QRS-T angle and cardiac troponin T concentration.